Kritik Sosial dalam Stand Up Comedy (Analisis Semiotika Show “Pragiwaksono World Tour”) - Reynord Leonardo; Ahmad Junaidi (Koneksi, 2020)
This study discusses the stand up comedy that is popular among the people. Stand up comedy itself is a singular comedic art whose contents from ordinary jokes contain social criticism. Pandji Pragiwaksono is one example of a comic where he likes to bring stand up comedy material containing social criticism where there are some social problems that we are experiencing in the form of comedy. The theory used by researchers is the theory of mass communication, mass media, social criticism, stand up comedy. This study uses a qualitative approach with the semiotic analysis technique method Ferdinand De Saussure which divides the selected sign into two namely signifier and signified. In this study it was found that the show stand up comedy made by Pandji Pragiwaksono namely Pragiwaksono World Tour slipped a number of social criticisms in which social criticisms were presented including criticism of children's names, criticism of children 's Youtubers, critics of PSSI chairmen, critics of the profession of people, criticisms of humanity , criticism about fans, criticism about animals, and criticism of the attitude of Indonesian citizens. The result is stand up comedy is not just a tool to entertain the public but can also slip social criticism in the form of comedy criticism delivered by Pandji made with satire and comedy so that the message received can be captured easily by his listeners.Penelitian ini membahas tentang stand up comedy yang sedang populer dikalangan masyarakat. Stand up comedysendiri merupakan seni melawak secara tunggal di mana isi dari lawakan berupa kritik sosial. Pandji Pragiwaksono menjadi salah satu contoh komika di Indonesia yang membawakan materi  stand up comedyberisi kritik sosial terhadap beberapa masalah sosial. Teori dan konsep yang digunakan peneliti adalah komunikasi massa, media massa, kritik sosial, stand up comedy. Penelitian ini menggunakan pendekatan kualitatif dengan metode teknik analisis semiotika Ferdinand De Saussure yang membagi tanda menjadi dua yaitu signifierdansignified. Penelitian ini menemukan bahwa pertunjukan stand up comedyPandji Pragiwaksono yaitu Pragiwaksono World Tourmenyelipkan beberapa kritik sosial antara lain kritik nama anak, kritik youtuberanak-anak, kritik ketua PSSI, kritik tentang profesi orang, kritik kemanusiaan, kritik tentang fans, kritik tentang satwa, dan kritik sikap warga Indonesia. Kesimpulan dari penelitian ini yaitu stand up comedybukan menjadi alat untuk menghibur masyarakat namun juga menyelipkan kritik sosial dalam bentuk komedi kritik yang dibuat dengan satir dan komedi sehingga pesan yang diterima dapat ditangkap dengan mudah oleh pendengarnya.